The COVID-19 Prevalence among Children: Hypotheses for Low Infection Rate and Few Severe Forms among This Age Group in Sub-Saharan Africa - Sylvain Raoul Simeni Njonnou; Nadia Christelle Noumedem Anangmo; Fernando Kemta Lekpa; Diomede Noukeu Njinkui; Dominique Enyama; Christian Ngongang Ouankou; Eric Vounsia Balti; Esther Astrid Mbono Samba Eloumba; Jean Roger Moulion Tapouh; Simeon Pierre Choukem (Interdisciplinary Perspectives on Infectious Diseases)
Despite some cases of severe or critical manifestations of the coronavirus disease 2019 (COVID-19) described among children, the prevalence of this infection in the pediatric population is quite low worldwide, particularly in sub-Saharan Africa. Current data suggest indeed that, independent of the population considered overall, severe and critical cases of COVID-19 are rare among children. This observation prompted us to discuss the possible hypotheses which could explain the low prevalence of COVID-19 among children; amongst others, we discuss (1) immunomodulation by the Bacillus Calmette–Guerin vaccine or by some parasitic infections such as malaria, schistosomiasis, and helminthiasis and (2) cross immunization with other coronaviruses commonly found in the sub-Saharan African setting.